The Influence of Leadership Style and Work Environment on Employee Performance at PT. Sinar Inti Primajaya Perkasa - Tria Mitra Fatia; Sunarti (www.amertainstitute.com, 2024)
This research seeks to examine how leadership style and work environment impact employee performance at PT. Sinar Inti Primajaya Perkasa, with a sample of 56 employees. Data was gathered using questionnaires, and the analysis was conducted using the SPSS V 24 statistical tool. The findings revealed that both leadership style and work environment significantly influence employee performance at the company.. Sinar Inti Primajaya Perkasa Influence of Leadership Style (X1): Based on the calculation results, it was found that the t-count value (2.590) is greater than the t-table value (2.005), with a significance level of 0.012 for the Leadership Style variable (X1), which is greater than 0.05 or 5%. Therefore, Ho is accepted and Ha is rejected, indicating that Leadership Style does not have a significant effect on Employee Performance, despite having a negative impact. Regarding the Work Environment (X2), the t-count value (6.067) is greater than the t-table value (2.005), with a significance level of 0.000, which is less than 0.05 or 5%. As a result, Ho is rejected and Ha is accepted, meaning that the Work Environment has a significant effect on Employee Performance.